Establishment and Characterization of a Nude Mouse Model of Subcutaneously Implanted Tumors and Abdominal Metastasis in Gastric Cancer - Yin Zhu; Yi Hu; Ming Cheng; Chun-Yan Zeng; Zhen Yang; Xiao-Dong Zhou; Jiang Chen; Nong-Hua Lu (Gastroenterology Research and Practice)
A mouse gastric cancer model is an important tool for studying the mechanisms of gastric cancer. To establish subcutaneously implanted tumors, MKN-45 cell suspensions and tumor tissues were implanted into the middle of the right armpit of nude mice. To generate an abdominal metastasis model, MKN-45 cell suspensions and tumor tissue homogenates were implanted into the middle of the lower abdomen. We measured the weights of the nude mice and the longest dimension, shortest dimension, thickness, and volume of the tumor. We also analyzed the rate of tumor formation, the time required for tumor formation, and the number and size of abdominal tumors in the mice. The rates of formation of the subcutaneously implanted tumors were 100%, 0%, and 100% in the nude mice inoculated with 2 × 107 cells/mL or 1 × 107 cells/mL of the MKN-45 cell suspension or the tumor tissue homogenate (2 × 107 cells/mL), respectively. The rates of metastatic abdominal tumor formation were 100%, 50%, and 75% in mice inoculated with 5 × 107 cells/mL or 1 × 107 cells/mL of the tumor tissue homogenate or the MKN-45 cell suspension (5 × 107 cells/mL), respectively. We derived tumor tissues and tumor tissue homogenates from nude mice prior to establishing the subcutaneous model of implanted tumors and the abdominal metastasis model of gastric cancer, respectively.